Mapping the value for money of precision medicine: a systematic literature review and meta-analysis - Chen, Wenjia; Wong, Nigel Chong Boon; Wang, Yi; Zemlyanska, Yaroslava; Butani, Dimple; Virabhak, Suchin; Matchar, David Bruce; Prapinvanich, Thittaya; Teerawattananon, Yot (Frontiers in Public Health, 2023)
Objective: This study aimed to quantify heterogeneity in value for money of Precision medicine (PM) by application types across contexts and conditions, and quantify sources of heterogeneity to areas of particular promises or concerns as the field of PM moves forward.Methods: A systemic search was performed in Embase, Medline, Econlit and CRD databases for studies published between 2011 and 2021, on cost-effectiveness analysis (CEA) of PM interventions. Based on a willingness-to-pay threshold of one-time GDP per capita of each study country, the net monetary benefit (NMB) of PM was pooled using random-effects metaanalyses. Sources of heterogeneity and study biases were examined using random-effects metaregressions, jackknife sensitivity analysis, and the Biases in Economic Studies checklist.Results: Among the 275 unique CEAs of PM, publicly-sponsored studies found neither genetic testing nor gene therapy cost-effective in general, which was contradictory to studies funded by commercial entities and early-stage evaluations. Evidence of PM being costeffective was concentrated in genetic test for screening, diagnosis or as companion diagnostics